The Influence Of The Work Environment On Motivation And Their Impact On Employee Performance At Distribution Center The Body Shop Indonesia - Muhammad Abdullah (Matriks Jurnal Sosial dan Sains, 2022)
All companies in the world are currently in a condition affected by the effects of the Covid-19 pandemic that emerged at the end of 2019. The purpose of this study was to determine how the direct influence of the work environment on employee performance, the direct influence of motivation on employee performance, and to determine the effect of the work environment through motivation and its impact on employee performance at The Body Shop Indonesia Distribution Center. The population and sample of the object of this research are all employees who work in the Distribution Center of The Body Shop Indonesia, totaling 39 people. The results of the study indicate that there is a direct and significant influence of the work environment on employee performance, then there is also a direct and significant influence of motivation on employee performance and proves that there is an influence of the work environment through motivation on employee performance at the Distribution Center of The Body Shop Indonesia.